Dichotomous roles of IL-36 and IL-38 in cardiovascular disease - Zhang, Haifeng; Huang, Wenhui; Bao, Shisan (Frontiers in Immunology, 2025)
Members of the interleukin-1 (IL-1) superfamily play crucial roles in orchestrating inflammation and immune responses. Among them, IL-36 and IL-38 have emerged as cytokines with contrasting roles in cardiovascular disease (CVD). IL-36 typically promotes inflammation, contributing to endothelial dysfunction, atherogenesis, and myocardial injury. In contrast, IL-38 exerts predominantly anti-inflammatory effects, modulating immune responses and promoting tissue repair. This mini-review provides a critical synthesis of current findings on IL-36 and IL-38 in the context of atherosclerosis, myocardial ischaemia–reperfusion (I/R) injury, and post-percutaneous coronary intervention (PCI) outcomes. We discuss their molecular mechanisms, potential as biomarkers, and therapeutic implications, while identifying key gaps in knowledge that merit further investigation.